The effect of intrahippocampal injection of estradiol on spatial memory in male rats during multiple sclerosis disease - Vahideh Zarrin; Homeyra Hatami; Alireza Ali Hemmati (Journal of Fasa University of Medical Sciences, 2014)
Background & Objective: Multiple sclerosis (MS) is a demyelinating disease of central nervous system, which is approximately two to three times more common in women than men. It was suggested that sexual hormones affect MS disease. Over half of MS patients have cognitive deficits, including learning and memory dysfunction. Estrogen also influences most of the cerebral function including learning and memory. According to the involvement of estrogen on learning and memory process, the objective of this study is to investigate the neuroprotective effect of estrogen during MS disease.  Materials & Methods: 28 male rats after cannnulating into the CA1 area of hippocampus, randomly divided into four groups (n=7) including control group, sham group (sesame oil, 1 μl/rat), MS group (0.01% ethidium bromide, 3 μl/rat), MS + estradiol group (ethidium bromide + estradiol benzoate, 2 μg/1μl). MS model was induced by intra hippocampal injection of ethidium bromide and estradiol benzoate was injected as a pretreatment for five days. The Morris Water Maze test was used for studying spatial memory. Data analysis was performed using one-way ANOVA and Tukey test.  Results: Ethidium bromide reduced the spatial memory (P<0.05). Pretreatment of estradiol benzoate (2 μg/1μl) significantly improved spatial memory during MS disease (P<0.05).  Conclusion: It seems that estradiol benzoate improves the reduced spatial memory during MS disease due to its neuroprotective effects.